Trends in Adolescent Fertility: EU Context and Regional Differentiation in Lithuania - Tretjakova, Vaida; Pociūtė-Sereikienė, Gintarė; Ubarevičienė, Rūta (Lithuanian Journal of Statistics, 2018)
[full article and abstract in Lithuanian; abstract in English]The aim of this article is to analyse changes in adolescent fertility in the Member States of the European Union and Lithuania. We have investigated trends in adolescent fertility rate (number of live births per 1000 women aged 15-19 years) during the period of 2001-2015, examined the extent of the changes and explored spatial differentiation at the municipality level in Lithua-nia. In addition to the analysis of the 15-19 year old age group, the present paper also includes analysis of the sub-groups of 15-17 and 18-19 year olds. Calculations are based on the vital registration data on fertility in the EUROSTAT database (for the EU coun-tries) and the data provided specifically for this project by Statistics Lithuania in accordance to the contract for the provision of con-fidential statistical data for scientific purposes (for the municipalities of Lithuania).
Keywords: adolescent fertility rate; adolescent birth rate; spatial differentiation; European Union; Lithuania